2008
DOI: 10.1016/j.cryogenics.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel insulation applications for liquid hydrogen launch vehicle tanks

Abstract: Aerogel based insulation systems for ambient pressure environments were developed for liquid hydrogen (LH2) tank applications. Solutions to thermal insulation problems were demonstrated for the Space Shuttle External Tank (ET) through extensive testing at the Cryogenics Test Laboratory. Demonstration testing was performed using a 1/10th scale ET LH2 intertank unit and liquid helium as the coolant to provide the 20 K cold boundary temperature. Cryopumping tests in the range of 20K were performed using both cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…Therefore, they have many potential applications in thermal, acoustic, electronic and catalytic fields, especially in thermal insulation [1][2][3][4]. However, hydrophilicity and powder or the granule form of silica aerogels limits their applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they have many potential applications in thermal, acoustic, electronic and catalytic fields, especially in thermal insulation [1][2][3][4]. However, hydrophilicity and powder or the granule form of silica aerogels limits their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Silica aerogels are excellent nanoporous materials with high specific surface area (500-1200 m 2 /g), low density (0.003-0.1 g/cm 3 ), low dielectric constant (1.1-2.0) and low thermal conductivity (0.013-0.04 W/m k). Therefore, they have many potential applications in thermal, acoustic, electronic and catalytic fields, especially in thermal insulation [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the total effective thermal conductivity of the aerogel is less than that of the free air at room temperature, and thus many aerogels have been directly used as thermal insulation materials especially in extreme conditions [4][5][6][7][8]. In the researches [9][10][11][12], we can find that gaseous thermal conductivity in the aerogel has significant contribution to the total thermal conductivity under normal ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Aerogel has been considered as a potential candidate to act as a heat shield in these cryogenic systems such as liquid-hydrogen (LH 2 ) tanks and liquid-oxygen (LO 2 ) feedlines because of its fully breathable and hydrophobic characteristics [152]. Furthermore, experiments in [153] have shown that liquid nitrogen (LN 2 ) can be prevented from accumulating within the intertank of the space shuttle by using an insulation system consisting of a bulk-fill aerogel material. The key phases to assess the performance of cryogenic insulation systems are at lift-off and reentry into the atmosphere when there are sudden changes in temperature and pressure.…”
Section: Thermal Insulationmentioning
confidence: 99%